Ukraine Open University: Its Prospects in Distance Education Development - Shunevych, Bohdan (International Review of Research in Open and Distributed Learning, 2002)
The genesis, initiation, and expansion of distance education at the Ukraine Open International University for Human Development, located in Kyiv, will be examined in this case study, starting with a brief look at the positive changes taking place in Ukraine's traditional educational system, as well as recent developments in the country's distance education (DE) system. To help readers understand the University's development from an insider's perspective, societal factors that currently influence its inter- and extra-institutional environment will also be examined. Next, the history, organizational structure, institutional activities, and background of the Ukraine Open International University for Human Development, along with the reasons driving the University's dual mode activities - both traditional and distance education - will be briefly analyzed. Included in this analysis is a summary of the challenges surrounding the application of both traditional and distance education models.The author concludes his case study by reflecting upon Ukraine Open International University for Human Development's experiences within the context of its being both a traditional education provider and new dual-mode distance education provider. Also discussed are some key indicators and predictions about what the future may hold for the University.